Technology Forecasting in the Mobile Telecommunication Industry: A Case Study Towards the 5G Era - SENNAROĞLU, BAHAR; VAYVAY, ÖZALP (TAYLOR & FRANCIS LTD, 2021)
The evolution of 3G and Long Term Evolution (LTE) has brought a remarkable advantage to mobility-based digital solutions by providing ubiquitous Internet services to a plethora of users with various needs. Nowadays, the dramatic adoption of smart devices and increasing consumption of mobile Internet have been accelerating mobile technology development activities toward a 5G ecosystem. Therefore, industry players need to make managerial decisions and design strategies based on forecasts related to the introduction of 5G technology. The aim of this research is to enhance the understanding of technological forecasting and technology life cycle in the mobile telecommunication industry. Specifically, the study was carried out in Turkey to contribute to the engineering management field on the topic. This contribution will be realized by forecasting the ideal launch time of 5G services for a leading telecommunication company in the market, which has been integrating new mobile technologies and densifying its existing network at an unprecedented rate in recent years. Our findings reveal that the most appropriate time for the 5G deployment and launch of mobile telecommunication services in Turkey would be in August 2020. This is the time when most of the forecast parameters used for making decisions on network investments are predicted to reach maturity.
Keywords: Mobile Telecommunication; 5G Ecosystem; Technology Forecasting; Technology Life Cycle; Strategy; New Product Development; Operations Management; Technology Management; Decision Making and Risk Management; DIFFUSION; ADOPTION; MODEL; FUTURE; TELEPHONY; BUSINESS; INTERNET; SERVICE